THE IMAGE OF MUSLIM WOMEN IN TV SERIES "WE ARE LADY PARTS" (2021) - Anisa, Zahratu Mutiara; Faisal, Bunyamin; Paturohmah, Pepi Siti (Saksama: Jurnal Sastra, 2024)
This research looks at how Muslim women are portrayed in director Nida Manzoor's TV series “We Are Lady Parts” (2021). The research is using the representation theory by Stuart Hall and Islamic feminism by Fatima Mernissi. This research aims to determine two things: first, how Muslim women are portrayed in the TV series “We Are Lady Parts” (2021); and second, how Muslim women are described in the show. The results of this study are classified into two, namely first, the images of Muslim women in the TV series “We Are Lady Parts” (2021) consist of the characterization of women consisting of physical aspects, Muslim women and their interactions, Muslim women in dealing with difficult situations, and Muslim women in their daily activities. Second, the representation of Muslim women depicted in the TV series “We Are Lady Parts” (2021) produces representations of educated Muslim women, Muslim women with a culture of love and marriage, Muslim women who have careers and hobbies, Muslim women and the struggle of misrepresentation.